Kontribusi Kedisiplinan Belajar Dan Pola Asuh Orang Tua Terhadap Hasil Belajar Siswa Kelas IV B SD Muhammadiyah 23 Surakarta Tahunajaran 2015/2016 - Fathimah, Khoirunnisa Nurlaila, Drs Suwarno,SH M.Pd (2016)
The purpose of this study was to determine include: 1) Contributions discipline of learning the learning outcomes of students of class IV B 23 SD Muhammadiyah Surakarta academic year 2015/2016, 2) Contributions parenting parents on learning outcomes of students of class IV B 23 SD Muhammadiyah Surakarta academic year 2015/2016, 3) Contributions discipline of learning and parenting parents on learning outcomes of students of class IV B 23 SD Muhammadiyah Surakarta academic year 2015/2016, type of research is based on a quantitative approach to this type of research Ex-Post Facto. The analysis technique used is, t Test, Test F. Based on the analysis of data: 1) The results of t-test learning discipline thitung (2.436) > t table (2.045), learning discipline has contributed positively to student learning outcomes. 2) parenting parents positive contribution to student learning, it is based on t test results tcount (2.795) > t table (2.045). 3) The test results f significance value 0.000 < 0.05, meaning discipline of learning and parenting parents together both contributed positively to the results of students of class IV B 23 SD Muhammadiyah Surakarta academic year 2015/2016.